(untitled) (Academia Science Repository, 2023)
This article presents information about the results of scientific studies that allow to evaluate and study the morphological features of the kidneys of 3-month-old rats after moderately severe brain injuries. Morphological analysis of rat kidneys was performed on days 7,14 and 21 after brain injury.